ANALISIS SISTEM INFORMASI AKUNTANSI PERSEDIAAN BARANG DAGANGAN PADA UD. OCEAN BLUE DI MEDAN - Hari Suwandi (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2020)
The purpose of this study is to determine the accounting information system for merchandise inventory at UD Ocean Blue. This research was conducted with a qualitative method based on theory. The problem that occurs in this company is the emergence of the difference in stock of goods between physical recording and bookkeeping records, this is because the company does not have a receipt of goods which is specifically tasked with overseeing and receiving goods that enter the field, so the goods that are entered are not carried out first inspection. The results of this study can be concluded that UD Ocean Blue has a fairly good accounting information system. Can be seen from the elements of the inventory information accounting system that has been implemented well. In this discussion the authors found several weaknesses in the inventory system implemented by the company. However, these weaknesses did not really affect the inventory system of merchandise at UD. Ocean Blue. So that conclusions can be drawn accounting information system for merchandise inventory has been implemented well